Adult's Epstein–Barr virus‐associated hemophagocytic lymphohistiocytosis: A case report - Yi Sun; Han Yao; Xiaofeng Yu; Yunzhao Chen; Chen Chai (Clinical Case Reports, 2023)
Key Clinical Message Adult's Epstein–Barr virus‐associated hemophagocytic lymphohistiocytosis is a rare and life‐threatening condition characterized by atypical initial symptoms and rapid disease progression. To facilitate early diagnosis and prompt treatment, it is imperative to implement early multidisciplinary intervention and prioritize pathogen detection, as these measures significantly contribute to enhancing patient prognosis.